Measuring e-learning systems success: Implementing D & M is success model - Sandjojo, Nidjo; Wahyuningrum, Tenia (2015 4th International Conference on Interactive Digital Media (ICIDM), 2015)
Electronic learning (e-learning) has been widely used as a complement subject to traditional learning methods. Implementing e-learning is becoming one of many solutions in effecting the study process offered by higher educational institutions, such as Universitas Pembangunan Nasional "Veteran" Jakarta = UPNVJ and Sekolah Tinggi Teknologi Telematika Telkom (ST3 Telkom) Purwokerto, Central Java. The objective of this research is to measure the e-learning system success implemented by UPNVJ and ST3 Telkom Purwokerto and then compare the similarities and differences between of two. The modified DeLone & McLean Information Systems Success Model and part of Technology Acceptance Model are adopted in this study. The respondents are students who have been experience in using e-learning and are selected randomly from the Faculty of Computer Science of UPNVJ and from ST3 Telkom Purwokerto. The total respondents are 387, which consist of 215 students from UPNVJ and 172 from ST3 Telkom Purwokerto. For the results at UPNVJ, there are two hypotheses that were proven insignificant and at ST3 Telkom there are three hypotheses that were proven insignificant. Findings at UPNVJ show that the e-learning benefit can be explained by its independent variables by 53.8%%, and at ST3 Telkom by 60.6%. These percentages show that the predictors explained 53.8% for UPNVJ's e-learning benefit and 60.6% e-learning benefit for ST3 Telkom Purwokerto. These findings could be considered as novelties, because they are different from the original model.